2022
DOI: 10.3390/diagnostics12112626
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Signature of Diabetic Kidney Disease in Cerebrospinal Fluid and Plasma of Patients with Type 2 Diabetes Using Liquid Chromatography-Mass Spectrometry

Abstract: Diabetic kidney disease (DKD) is the major cause of end stage renal disease in patients with type 2 diabetes mellitus (T2DM). The subtle metabolic changes in plasma and cerebrospinal fluid (CSF) might precede the development of DKD by years. In this longitudinal study, CSF and plasma samples were collected from 28 patients with T2DM and 25 controls, during spinal anesthesia for elective surgery in 2017. These samples were analyzed using liquid chromatography-mass spectrometry (LC-MS) in 2017, and the results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Metabolomics analysis showed that the contents of various metabolites related to fatty acid metabolism and inflammatory response were abnormal in the plasma of T2DM mice. Studies have shown that the level of L-acetylcarnitine in diabetic patients was a specific diagnostic indicator of diabetic complications, and the large accumulation of L-acetylcarnitine in plasma may imply impaired mitochondrial function and fatty acid oxidation in diabetic patients [ 61 ]. L-Palmitoylcarnitine is a long-chain acylcarnitine, which is the product of fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics analysis showed that the contents of various metabolites related to fatty acid metabolism and inflammatory response were abnormal in the plasma of T2DM mice. Studies have shown that the level of L-acetylcarnitine in diabetic patients was a specific diagnostic indicator of diabetic complications, and the large accumulation of L-acetylcarnitine in plasma may imply impaired mitochondrial function and fatty acid oxidation in diabetic patients [ 61 ]. L-Palmitoylcarnitine is a long-chain acylcarnitine, which is the product of fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral small vessel disease (CSVD) is a disorder characterized by endothelial dysfunction that may be detected via MRI or cerebral Doppler ultrasound. These methods either show cerebral lacunes, microinfarcts, microbleeds, and white matter hyperintensities, as is the case with MRI, or they reveal poor vasodilatation, through the use of complex neurosonological methods [ 30 ] Because these techniques of diagnosis fail to detect early endothelial damage, sorbitol determination may be useful in assessing BBB function and the CVR, thus serving as a future possible therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Koppe et al described the implication of p-cresyl sulfate in the processes of insulin resistance in patients with CKD [45]. Although several authors have described p-cresyl sulfate concentration in serum [46,47], few studies have been developed with regard to urinary concentrations of p-cresyl sulfate.…”
Section: Uremic Toxins (Hippuric Acid Indoxyl Sulfate and P-cresyl Su...mentioning
confidence: 99%